The use of bioelectrical impedance analysis to predict post-operative complications in adult patients having surgery for cancer: A systematic review. Issue 5 (May 2021) - Matthews, L.; Bates, A.; Wootton, S.A.; Levett, D.
Summary: Background: Patients undergoing surgery for cancer are at particular risk of post-operative complications. The pre-operative period is an opportunity to identify and mitigate risk factors and improve outcome. Bioelectrical impedance analysis (BIA) may offer an additional means of identifying patients at risk of post-operative morbidity. Aims: The aim of this systematic review was to assess the use of measures and estimates of body composition determined by BIA as markers of peri-operative risk in adult patients undergoing elective surgery for cancer. Methods: This review was performed in accordance with the PRISMA guidelines. The electronic databases of MEDLINE, EMBASE, CINAHL, CENTRAL and the Web of Science were searched from inception. Studies of adult participants having elective surgery for cancer were included if participants underwent BIA in the peri-operative period and were assessed for post-operative complications. Results: 2578 studies were identified, of which 12 were eligible for inclusion. In total the studies report data from 1508 subjects. Five studies examined phase angle or standardized phase angle, six examined derived measures and one examined both. Eight of the 12 demonstrated an association between phase angle and/or body composition and an increased risk of post-operative complications. Conclusions: Bioelectrical impedance analysis in the peri-operative period may be useful in predicting the risk of complications following elective cancer surgery. Phase angle more consistently demonstrates an association than derived estimates. Further high quality studies are needed and should report the raw impedance values, standardized phase angle and the equations used to derive body composition.